Managing the Decommissioning and Remediation of Damaged Nuclear Facilities : Final Report of the Collaborative Project DAROD. - IAEA (IAEA, 2021)
As part of the Action Plan on Nuclear Safety, the IAEA led the International Project on Managing the Decommissioning and Remediation of Damaged Nuclear Facilities (DAROD Project). The DAROD Project focuses on providing practical guidance for the decommissioning and remediation of accident damaged nuclear facilities based on case studies of actual damaged facilities and lessons learned. This publication summarizes the outcomes of the DAROD Project. It is intended for regulatory bodies, operating organizations, technical support organizations and governmental officials who are involved in the decommissioning and remediation of nuclear facilities damaged after an accident or owing to a legacy deterioration.
Keywords: Nuclear facilities.; elektronické knihy; electronic books